Inklusi Global: Pemberdayaan Keterampilan Membatik dan Edukasi Mitigasi Kegawatdaruratan bagi Peserta Didik Disabilitas di LKP Aora Wistara Surabaya - Elga Ceisaria Andani; Ainun Ganisia; Rakhmalia Imeldawati; Nurul Fathiyyah; Putri Gunawan; Angel Erbabley (Health Care : Journal of Community Service, 2026)
LKP Aora Wistara is a training institution for students with disabilities in Surabaya focusing on economic independence through the art of batik, yet it still faces challenges in environmental safety literacy. This community service activity aims to empower disabled students through the integration of vocational skills and emergency mitigation education. The method employed was an inclusive participatory approach involving strategic coordination, digital application-based emergency training, and batik mentoring themed "Resilience Motif." A total of 30 students actively participated with the support of sign language instructors. Evaluation results using a Likert scale showed significant improvements across all indicators, with the highest surge in digital application usage skills (from 1.8 to 4.2) and participant self-confidence (final score of 4.8). The program successfully produced an Inclusive Health Education Application and enhanced independent mitigation capabilities. It is concluded that the synergy between inclusive digital technology and creative art activities is effective in building psychological resilience and independence for vulnerable groups with disabilities.